SAPMS; Student Assessment Process Management System Enriched with Quality Factors - Elsaid, Abdelghafar Mohammed Elhady; Hassan, Ahmed Elsayed (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Computer’s hardware and software development aided education field progresses more rapidly. Not only the computer is used in learning and assessment processes to add more attractiveness, but also it’s used for better performance of educational system. But one of more defects was lacking in applying modern educational quality factors to both learning and assessment software. This paper presents a web based Student Assessment Process Management System (SAPMS). SAPMS provides a secured, attractive, easy to use and quality based assessment system. Our system is completely analyzed and designed using the Unified Modeling Language (UML). We also present the implementation of the core components of the SAPMS which performs the most important processes in the system. In addition to that a validation study for the system components is performed.